Proportioning of steel fibre reinforced concrete mixes for pavement construction and their impact on environment and cost - Achilleos, Constantia; Neocleous, Kyriacos; Pilakoutas, Kypros; Neophytou, Pavlos O.; Kallis, Stelios; Hadjimitsis, Diofantos G. (My University, 2011)
Steel fibre reinforced concrete (SFRC) is a construction material investigated for more than 40 years including for pavement applications. A number of studies have demonstrated the technical merits of SFRC pavements over conventional concrete pavements; however little work has been carried out on the environmental and economical impact of SFRC during the pavement’s life cycle. Therefore, extended research was undertaken within the framework of the EU funded project “EcoLanes” to estimate the environmental and economical loadings of SFRC pavements. The innovative concept of the project is the use of recycled steel tyre-cord wire as concrete fibre reinforcement, which provides additional environmental benefits for tyre recycling over landfilling. Within the project framework a demonstration of a steel-fibre-reinforced roller-compacted concrete (SFR-RCC) pavement was constructed in a rural area in Cyprus. In order to assess the economical and environmental picture of the demonstration pavement, life cycle cost analysis (LCCA) and life cycle assessment (LCA) studies were undertaken, which also compared the under study pavement design with four conventional alternatives. The main output of the studies is that SFR-RCC is more environmentally and economically sustainable than others. In addition, various concrete mix designs were investigated by considering parameters such as fibre type and dosage, cement type, and transportation distances to the construction site. Fibre dosage has been highlighted as a crucial factor compared with economical and environmental loadings in SFR-RCC pavement construction.
Keywords: Life cycle assessment; Steel fibre reinforced concrete; Tire recycling